Neglected infrastructures for 6G—Underwater communications: How mature are they?. (April 2023) - Dao, Nhu-Ngoc; Tu, Ngo Hoang; Thanh, Tran Thien; Bao, Vo Nguyen Quoc; Na, Woongsoo; Cho, Sungrae
Abstract: In recent years, we have witnessed a major expansion of wireless communications, extending from terrestrial to aerial spaces to facilitate novel user services. While aerial access infrastructure is widely accepted to be an essential part of a comprehensive sixth-generation (6G) network, underwater wireless communications (UWC), unfortunately, are neglected. This observation questions us about the maturity of UWC technologies and its potentials for 6G. First, we describe an overview of 6G access infrastructures, revealing the gaps concerning underserved spaces and services. Next, we investigate current developments of cutting-edge technologies that enable heterogeneous multiaccess UWCs. Furthermore, we introduce UWC-enabled application scenarios that possibly improve the popularity of 6G in aquatic environments. Then, we analyze a feasible approach for a UWC integration to complement the 6G infrastructures, achieving a fully comprehensive framework. Finally, open challenges are discussed to drive future studies toward the maturation of UWC. This study is expected to facilitate interested researchers and engineers with a systematical reference framework of state-of-the-art UWC knowledge and information.